Combined electronic and thermodynamic approaches for enhancing the thermoelectric properties of Ti-doped PbTe. Issue 47 (21st November 2016) - Komisarchik, G.; Gelbstein, Y.; Fuks, D.
Abstract : DFT combined with statistical thermodynamics is used for investigating the effects of phase separation and impurity states on the electronic properties of Ti-doped PbTe. Abstract : Lead telluride based compounds are of great interest due to their enhanced thermoelectric transport properties. Nevertheless, the donor type impurities in this class of materials are currently mainly limited and alternative types of donor impurities are still required for optimizing the thermoelectric performance. In the current research titanium as a donor impurity in PbTe is examined. Although titanium is known to form resonant levels above the conduction band in PbTe, it does not enhance the thermo-power beyond the classical predictions. Recent experiments showed that alloying with a small amount of Ti (∼0.1 at%) gives a significant increase in the figure of merit. In the current research ab initio calculations were applied in order to correlate the reported experimental results with a thermoelectric optimization model. It was found that a Ti concentration of ∼1.4 at% in the Pb sublattice is expected to maximize the thermoelectric power factor. Using a statistical thermodynamic approach and in agreement with the previously reported appearance of a secondary intermetallic phase, the actual Ti solubility limit in PbTe is found to be ∼0.3 at%. Based on the proposed model, the mechanism for the formation of the previously observed secondary phase is attributed to phase separation reactions, characterized by a positive enthalpy of formation in the system. With extrapolation of the obtained ab initio results, it is demonstrated that lower Ti-doping concentrations than previously experimentally reported ones are expected to provide power factor values close to the maximal one, making doping with Ti a promising opportunity for the generation of highly efficient n-type PbTe-based thermoelectric materials.